Distance Learning Student's Needs: Evaluating Interactions from Moore's Theory of Transactional Distance. - Syed Hassan, Sharifah Sariah; Ustati, Rusmanizah (Turkey, 2013)
This study draws on the experience from a focus group interviews under the distance learning programme known as Program Pensiswazahan Guru (PPG) organized by the Malaysian Ministry of Education in collaboration with local universities and institutes of education. Its purpose is to uncover students’ perception about the platform used by International Islamic University Malaysia (IIUM) which is the Learning Management System (LMS). LMS is a vital instructional medium especially for the varsity distant learners. Michael Moore’s Theory of Transactional Distance is used as the guiding framework to gain insights on learning and interactions in this e-learning setting. Teacher-student interactions are analyzed for better understanding of the phenomena under study. The findings indicate that in terms of usability LMS is perceived as a good platform to acquire information on content and to receive feedback from instructors. However, IIUM learners hope for more interactivity where learners can communicate amongst themselves beside engaging with the instructor-learner- content interactions that they currently experience via the system. This study aspires to provide insights on the significance of interactions from distance learners’ perception.